Village Baseline Study: Site Analysis Report for Yatenga – Tougou, Burkina Faso - Goudou D; Traoré Gue, J.N.; Ouédraogo, Mathieu; Segda, Zénabou; Somé, Léopold; Sawadogo, P.; Sawadogo-Ganou B; Sissoko, Keffing; Zougmoré, Robert B.; Moussa, Abdoulaye S. (2012)
The village baseline study of Kononga village in the CCAFS site Yatenga-Tougou in Burkina Faso took place from 19th to 21st July 2011. Focus group discussions were conducted separately for men and women. Male and female participants believe that the natural resources in the village are deteriorating due to population increase and labour shortages related to the exodus of young people to gold mining sites. The village’s vision of the future includes more productive and fertile farmland, a denser forest, deeper and wider water reservoirs, and more boreholes. The men identified 21 organisations in the village, including 9 operating at the community level, while women identified 17 organisations, 10 of which operate at the community level. Men are considered the most important personal source of information in the village. The regional directorate for agriculture, hydrology and fishery resources (DRAHRA) is the single most relevant institutional source of climate and weather information for both male and female participants. Men and women gather information from outside the village via radio broadcasting and particularly Radio “Voix du paysan” (Voice of the Farmer). The market is the most important channel of information access for women. Women have a substantial role in agriculture and livestock production, as well as natural resource management but they have limited access to land or to improved technology or equipment, and few training opportunities.